PENGARUH FERMENTASI MENGGUNAKAN BAKTERI ASAM LAKTAT YOGHURT TERHADAP CITARASA KOPI ROBUSTA (COFFEA ROBUSTA): (The Influence of Fermentation Using Bacteria Lactic Acid Yoghurt to the Flavor of Coffe Robusta (Coffea robusta)) - Abu Bakar Tawali; Nurlailah Abdullah; Benny Suhardi Wiranata (jurnal1, 2018)
Coffee plants ( coffea sp ) is one type of biodiversity in Indonesia.Coffee is one of the most popular drink in the world.The high caffeine content in coffee has bad effect for health.One kind of coffee used in this research was Robusta, because caffeine content in robusta coffee is higher than arabica coffee, otherwise the type of arabica contain more sugar and volatile oil.To improve the quality of coffee then one of the process that need attention is on the process in the past harvest.One technology in the post harvested to fix tastes coffee is by fermentation using lactic acid bacteria ( BAL ).This research aimed to produce coffee with the caffeine levels lower by fermentation using BAL on yoghurt. Parameter this research include caffeine level, ph level, the water level, the ashes level and testing the like parameter of organolepticflavor, aroma, and colour of the coffee. The best experiment resulting from research coffee fermented with isolate yogurt for 48 hours, it had caffeine content of 1,09 % ,Ph of 4.73, water contentof 2.34, ashes content of 3.16, flavor parameter scored of 3.08, aroma parameter scored of 3, and color parameter scored of 2.09.